Earth System Governance : World Politics in the Anthropocene - Biermann, Frank, 1967- (Book collections on Project MUSE., 2014)
In an era of planet-wide transformation, we need a new model for planet-wide environmental politics. This book proposes 'earth system' governance as just such a new paradigm. It offers both analytical and normative perspectives. It provides detailed analysis of global environmental politics in terms of five dimensions of effective governance: agency, particularly agency beyond that of state actors; architecture of governance, from local to global levels; accountability and legitimacy; equitable allocation of resources; and adaptiveness of governance systems.